2011
DOI: 10.1001/archinternmed.2011.204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronary Computed Tomographic Angiography Results on Patient and Physician Behavior in a Low-Risk Population

Abstract: An abnormal screening CCTA result was predictive of increased aspirin and statin use at 90 days and 18 months, although medication use lessened over time. Screening CCTA was associated with increased invasive testing, without any difference in events at 18 months. Screening CCTA should not be considered a justifiable test at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 34 publications
3
34
1
Order By: Relevance
“…In a comparable propensity score-based study of subclinical atherosclerosis imaging with coronary computed tomographic angiography, we reported similar results (comparing coronary computed tomographic angiography to usual care). 17 However, in contrast to our short-term study (18 months), Shreibati et al 19 found that CAC imaging was also associated with lower rates of the composite outcome of death, myocardial infarction, or stroke during a median of 3 years' follow-up (hazard ratio, 0.74; confidence interval, 0.58-0.94; P=0.017). This result is particularly notable given the findings of the Justification for the Use of Statins in Prevention: An Intervention Trial Evaluating Rosuvastatin (JUPITER) study, where hs-CRP was found to identify persons with normal cholesterol levels who derive benefit from statin therapy.…”
Section: Mcevoy and Blaha Comparative Effectiveness Of Cac Versus Hsccontrasting
confidence: 84%
See 1 more Smart Citation
“…In a comparable propensity score-based study of subclinical atherosclerosis imaging with coronary computed tomographic angiography, we reported similar results (comparing coronary computed tomographic angiography to usual care). 17 However, in contrast to our short-term study (18 months), Shreibati et al 19 found that CAC imaging was also associated with lower rates of the composite outcome of death, myocardial infarction, or stroke during a median of 3 years' follow-up (hazard ratio, 0.74; confidence interval, 0.58-0.94; P=0.017). This result is particularly notable given the findings of the Justification for the Use of Statins in Prevention: An Intervention Trial Evaluating Rosuvastatin (JUPITER) study, where hs-CRP was found to identify persons with normal cholesterol levels who derive benefit from statin therapy.…”
Section: Mcevoy and Blaha Comparative Effectiveness Of Cac Versus Hsccontrasting
confidence: 84%
“…One such strategy is the use of propensity-based matching to convert observational data into a form more akin to randomized controlled trial data by mimicking the effect of randomization. 17 Using observed covariates, propensity scores match subjects who receive an intervention (eg, CAC) with subjects who do not to balance the distribution of potential confounders of the outcome (eg, ASCVD events) in both groups. 18 However, unlike randomization, this strategy cannot balance unmeasured confounders.…”
Section: Article See P 655mentioning
confidence: 99%
“…Screening stress testing [67,[101][102][103] and CT coronary angiography [104] are considered inadequate means of assessing CAD risk in asymptomatic adults. Coronary calcium score may be helpful to determine the burden of CAD, but at this time the risk associated with a particular calcium score is unknown [105] and deemed an inappropriate marker for those at low risk [106].…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…Although CT calcium scoring allows identification of asymptomatic plaque burden, population-wide screening is currently not yet recommended. 5 Coronary CTA itself does not determine whether a stenotic lesion causes myocardial ischemia. Very recently, noninvasive fractional flow reserve derived from coronary CTA has high diagnostic performance for the detection and exclusion of coronary lesions that cause myocardial ischemia.…”
Section: Article P 2832mentioning
confidence: 99%